Effect of pressurization positions on the consolidation of dredged slurry in air-booster vacuum preloading method. Issue 1 (2nd January 2020) - Xie, Zhiwei; Wang, Jun; Fu, Hongtao; Cai, Yuanqiang; Xiuqing, Hu; Cai, Yin; Zhang, Yan; Ma, Xiaohua; Jin, Haisheng
Abstract: Air booster vacuum preloading method is a useful method for strengthening dredged slurry. Though this method is improved effectively with the rapidly developed technology, the problem of inadequate reinforcement in deep layers of soil is still in existence. In view of the fact that the pressurizing system can effectively enhance the reinforcement effect. Therefore, this paper discusses the reinforcement effect of a new pressurizing system that put the booster pipeline at the bottom of soil. Meanwhile, another problem is found that the booster pipeline type was single at present, the action effect of different kind of booster pipeline is still uncertain. In this paper, laboratory experiments are performed to investigate the influence of two kinds of pressurization position and two types of booster pipeline on the treatment of five dredged slurry samples. The test results showed that though the vertical pressurizing system can be good to reinforce the middle soil layers, but the bottom pressurizing system can make the whole soil layer more homogeneous. Furthermore, the difference of the two kinds of booster pipeline on the reinforcement effect of soil is not significant. These results provide good guidance for practical application of air booster vacuum preloading in land reclamation project.